(3GdCef GdGbJUGOj GdYQHjs (3GdENaGbGJ hNjGQGJ GdeSJbHds - (3GdLejdj(B, (3MejOs ((3YeGf(B;(3YeGfs (3eDSSI GdhQGb ddfTQ hGdJhRjY(B;(3HhGHI GdeUGOQ ddfTQ hGdJhRjYs, 2022)
(3jgOa gPG GdcJGH HGdOQLI GdCSGSjI Edi ERGdI GdQDjI GdVHGHjI GdJj JcJfa eSjQI GdJfejI GdYQHjI, ef NdGd EdbGA GdVhA Ydi OQLI GfcTGa hJHYjI GdEbJUGO GdYQHj hgTGTI GdHfjI GdgjcdjI, hJbOje QDi LOjOI dYedjI HfGA GdCef GdGbJUGOj GdYQHj(B. (3ceG Cf gPG GdcJGH jOYh Edi VQhQI EYGOI gfOSI fXQjI GdJcGed GdGbJUGOj GdYQHj dHfGA GdCef GdEbJUGOj GdYQHj(B. (3Ydi CSS LOjOI hJhajQ egGe HfGA GdJfejI GdeSJbdI HYjOG Yf GdeKGdjGJ hGdCeGfj GdeLQOI(B. (3hHYjOG Yf OYGI ejGg GdGROgGQ GdYGdjI, hGdLHGd ef GdSdY hGdaQOhS GdEbJUGOj Gdehghe, hHYjOG Yf OYGI HQGeL JZQjH GdJfejI GdYQHjI, hHQGeL hSjGSGJ NjHGJ GdYhdeI(B.s
Keywords: (3GdHdGO GdYQHjI (B- (3SjGSI GbJUGOjIs; (3GdCef GdGbJUGOj (B- (3GdHdGO GdYQHjIs; (3GdHdGO GdYQHjI (B- (3CMhGd GbJUGOjI s